Role of Augmented Reality Applications in Spreading Brand Related Electronic Word of Mouth: A Conceptual Model - De Mel, W. D. H.; Samarasinghe, G. D.; Eranda, B. A. N. (Faculty of Commerce and Management Studies University of Kelaniya., 2024)
With its unparalleled ability to enhance the actual world with virtual annotations, augmented reality has emerged as a cutting-edge interactive technology. The rapid evolvement of this technology has transformed consumers’ shopping experience with many brands successfully having integrated augment reality into e-commerce. In fashion retail, augmented reality technology facilitates virtual try-ons which is a novel experience to customers. Nevertheless, limited research has examined what gratification of augmented reality drive consumers to use these applications and how they impact consumer-to-consumer interactions on social media platforms. This paper addresses this gap in literature, proposing a conceptual model to examine uses and gratifications of augmented reality applications and their impact on brand related electronic word of mouth. Drawing on Stimulus-Organism-Response model, the study integrates Uses and Gratifications Theory. In addition, to identify how consumers perceive the adoption of augmented reality, technology readiness is also integrated to the proposed model as a moderator. The paper also highlights the managerial implications pertaining to the empirical testing of the proposed model in the context of online fashion retail. Finally, the study proposes a research agenda for further study on this phenomenon of augmented reality applications in online fashion retail on consumer behavior.